Methodology to Improve Interaction in Educational Processes Based on Virtual Reality Techniques - Arrieta-Amaya, Elizabeth (2025)
Information and communication technologies are helping to improve experiences in many areas, such as engineering, simulation, education. It is in the area of education, that thanks to the help of hardware and software, are allowing to improve the educational experiences, in the present work, we resort to the use of the Virtual Reality glasses of the Oculus Gest 2 model, with the Spatial application, applied to the learning of music. We present the architecture of the solution so that it can be replicated and scaled to other courses and subjects of study, we present how to configure each of the tools as well as the alternatives that can be worked in order to optimize resources, as a result we present the advantages and disadvantages of using Virtual Reality technology and recommendations to optimize its application so that it can be replicated and scaled to other applications.